Experimental study on the detection of cerebral hemorrhage in rabbits based on broadband antenna technology. (1st October 2019) - Zhang, Haisheng; Chen, Mingsheng; Jin, Gui; Xu, Jia; Qin, Mingxin
Abstract: Hematoma enlargement often occurs in patients with spontaneous intracerebral hemorrhage (ICH), so it is necessary to monitor the amount of intracranial hemorrhage in patients after admission. At present, the commonly used intracranial pressure (ICP) method has the disadvantages of trauma and infection, and the Computer Tomography (CT) method cannot achieve continuous monitoring. So it is urgent to develop a non-contact and non-invasive method for continuous monitoring of cerebral hemorrhage. The dielectric properties of blood are different from those of brain tissue, so the hematoma will affect the amplitude and phase of the electromagnetic waves passing through the head. A microstrip antenna was designed to construct the detection system for cerebral hemorrhage. Based on the animal model of acute cerebral hemorrhage, the detecting experiment was carried out on thirteen rabbits. Each rabbit had three bleeding states: 1, 2, and 3 ml, which represented the severity of cerebral hemorrhage. According to the measured data of high dimension and small sample, the support vector machine (SVM) algorithm was used to assess the severity of cerebral hemorrhage. According to simulation results, the antenna's forward radiation was 5 dB larger than the backward radiation, which ensured the antenna being not affected by external signals during the measurement. According to test results, the −10 dB workband of the antenna was 1.55–2.05 GHz and the frequency range of the transmission parameters S 21 above −30 dB is 1.2 − 3 GHz. In the animal experiment, the phase difference of Transmission coefficient S 21 was gradually increased with the increase of bleeding volume. Through the classification of 39 bleeding states of the 13 rabbits, the total accuracy was about 77%. Through animal experiments, the feasibility of detection method has been proved. But the classification accuracy need to be further improved. The detection system is based on broadband antenna has the potential to realize non-contact, non-invasive and continuous monitoring for cerebral hemorrhage.